Relationship between the Role of Nurse Coordinator and Nurse Performance at Ujoh Bilang Health Cente - Emiliana Devung; Hilda; Arifin Hidayat (Formosa Journal of Science and Technology, 2023)
The nurse coordinator is a manager who is directly related to nursing care activities and nursing management. Purpose This research was conducted to determine the relationship between the role of the nurse coordinator and the performance of nurses at the puskesmas. This type of quantitative research with a descriptive correlation research design using a cross sectional approach. The results of the research on the role of nurse coordinator based on this study showed a good planning role of 93.5%, an organizing role of 51.6%, a directing role good by 87.1%, and a good supervisory role by 77.4%. The results of the analysis of the relationship between the role of the nurse coordinator and the performance of nurses obtained a p value of 0.015 (p <0.05). The conclusion of this study is that the role of a good nurse coordinator can improve the performance of nurses at the puskesmas.